Prioritization of Reimplantation in Previously Successful Cochlear Implantation Following Natural Device Failure. Issue 8 (September 2018) - Hochman, Jordan B.; Pisa, Justyn; Cham, Bonnie
Abstract : Introduction: Cochlear reimplantation procedures account for approximately 5% of all implant cases and may be caused by internal device failure, skin flap complications, or an unexpected decline in auditory performance. This issue, in concert with changing demographics, expanded audiometric candidacy criteria, adult bilateral implantation, and implantation for unilateral hearing loss, all place escalating pressure on device availability and resource allocation in a publically funded health care system. Objective: The predictable and problematic access to a scare medical resource requires rigor in establishing program priority and formal policy. We present a single cochlear implant center's working reflections and an attempt at a principled approach to rationing health care decisions. Methods: Different approaches to health care rationing are examined and discussed. We describe a method of allocation that is currently employed by a large Canadian quaternary care center and ground this method in important principles of distributive justice as they apply to health care systems. Results: We elect to recognize device failure as analogous to sudden sensorineural hearing loss, with the associated need to expedite reimplantation. We consider this an ethical approach grounded in the egalitarian principle of equality of opportunity within cohorts of patients. Conclusion: Porting the practice from sudden sensorineural hearing loss, the time-sensitive need for hearing restoration, and maximized communication outcomes, dictates prioritization for this patient population. The predicted evolution of health systems globally and the shape of future medical practice will be heavily influenced by both the macro and micro level resource-dependent decisions implant centers currently face.